The Meaning Of Profit From The Perspective Of Business Actors In The Canteen Of The Faculty Of Economics And Business Tadulako University - Nurainun Habiba; Sugianto Sugianto; Ernawaty Usman; Latifah Sukmawati Yuniar (UNIVED Press, 2026)
This research aims to understand the meaning of profit from the perspective of business actors who carry out economic activities in the Canteen of the Faculty of Economics and Business, Tadulako University. This research uses a qualitative approach with phenomenological methods. Data were collected through semi-structured in-depth interviews, observations, and documentation conducted with two purposively selected informants. Data analysis uses the stages of data collection, data reduction, data presentation and conclusion drawn. The results of the study show that profit is interpreted multidimensionally, including interrelated material and non-material aspects. Functional material profit is understood as sustainability that supports the fulfillment of living needs and maintains business continuity. Meanwhile, non-material profits are interpreted as happiness, blessings and relationships. The campus environment as a social space also influences the way business actors view profits, so that business orientation is not solely directed at maximizing profits, but also at balancing economic interests and human values. This research contributes by broadening the understanding of profit as a contextual and social concept, especially in the practice of micro businesses operating in an environment full of social interaction.